2021
DOI: 10.1155/2021/6685575
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Sandwich Enzyme-Linked Immunosorbent Assay for Detection and Quantification of Clam Residues in Food Products

Abstract: Seafood is a frequent cause of allergic reactions to food globally. The presence of undeclared trace amounts of clam can cause allergic reactions in sensitive individuals. Limited tools are available to test food products for the presence of traces of clam. We report on the development of a sandwich ELISA that can detect and quantify clam protein in food. Antisera against a mix of two commercially important clam species, Atlantic Surf (Spisula solidissima) and ocean quahog (Arctica islandica), were raised in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The sandwich ELISA [ 80 ] is carried out by adsorbing the antigen-specific antibody into the wells. This antibody is generally a specific IgG and will capture the antigen contained in the applied sample [ 81 , 82 ], which can be represented by a food extract. Then, a primary antibody (generally IgG) specific for the searched allergen is added, and it binds to the antigen.…”
Section: Classical Analytical Methods Generally Used For Allergen Det...mentioning
confidence: 99%
“…The sandwich ELISA [ 80 ] is carried out by adsorbing the antigen-specific antibody into the wells. This antibody is generally a specific IgG and will capture the antigen contained in the applied sample [ 81 , 82 ], which can be represented by a food extract. Then, a primary antibody (generally IgG) specific for the searched allergen is added, and it binds to the antigen.…”
Section: Classical Analytical Methods Generally Used For Allergen Det...mentioning
confidence: 99%
“…The optical density values of the samples detected from a sandwich ELISA assay are related to the positive interaction between β-CN A2 protein isoform and the ELISA's enzyme-labeled antibodies, as well as the relative comparison of this interaction to the protein concentration in the standard curve. Other studies have found that the sandwich ELISA assay is the most reliable test for IgE-mediated allergenic substances in food, such as casein, albumin, globulin, gliadin, gluten, and clam proteins, with high precision, sensitivity, and relative ease of use (Bernard et al, 2021;Bosman et al, 2021;Koppelman et al, 2021;Madrid et al, 2021). Herein, the higher concentration of β-CN A2 protein isoform in Angus is likely linked with the larger plasma concentration of proline residue present in milk.…”
Section: β-Cn A2 Protein Isoform Concentration Analysis In Milkmentioning
confidence: 99%
“…In an attempt to in-vitro quantify β-CN A2 protein isoform concentration in order to obtain insights into its bioactive potential, the sandwich ELISA assay at optical density OD 450 wavelength was effectively performed in this study and did not cross-react with β-CN A1 protein. The detection using the sandwich ELISA assay allows a more direct reference of the presence of protein residues (Koppelman et al, 2021). In this assay, β-CN A2 protein isoform can be determined by the colorimetric reaction after the antigen binding with the particular enzyme-labeled antibody.…”
Section: β-Cn A2 Protein Isoform Concentration Analysis In Milkmentioning
confidence: 99%